Karakterisasi Sumberdaya Kambing Lokal Khas Kejobong di Kabupaten Purbalingga Propinsi Jawa-Tengah - Akhmad Sodiq (Agricultural Faculty, 2009)
Characterization of local goat of kejobong at local government of purbalingga, central javaABSTRACT. The purposes of this study were to identify the quantitative morphogenitical characteristics (external body dimensions) and qualitative characteristics (coat-colour), the population size, its distribution and diversity of morphogenitical characteristics, the population status in term of conservation, and to find out the model of conservation. The target of this study were goat-husbandry of local goat at Kejobong (13 villages) Local Government of Purbalingga, Central Java, Purbalingga Regency. Livestock On-Farm Trials (LOFT) by simple random sampling was implemented in this study. Sample sizes were determinate by Nomogram Harry King, and were involved of 931 head of local goat of Kejobong. Descriptive (qualitative and quantitative) analyses, variance analyses by General Linear Model (GLM) procedure of SPSS, analysis of the population status according to the Global Data Bank for Farm Animal Genetic Resources for Domestic Animal Diversity of FAO were applied.This study revealed that: (1) based on the size of external body dimensions, the Kejobong local goat appears the termediate between Kacang and Peranakan Etawah goats; (2) ) Based on the quantitative and qualitative characteristics, the Kejobong local goat assumed as a crossbreed-goat resulted from crossing between Kacang and Peranakan Etawah breeds. Dominant black and total black coat colour were predominants 74.45 and 56.49 percent among their population, respectively; (3) The Kejobong local goats were founded in all regions (13 villages) with the total populations about 15.317 heads. There was highly diversity in term of the characteristic of external body dimensions. This finding force to conduct the in-breed selection in order to improve their productivity; (4) Based on the Global Data Bank for Farm Animal Genetic Resources, the population status of local goat at Kecamatan Subdistric (15.317 heads) and the total population of black coat (8.623 heads) were classified into Not at Risk category. Board of Agriculture National Research Council (1993) classify that the population status into rare if the size of population ranges from 5.000 until 10.000 heads, it is imply that the total population of black coat goat (8.623 heads) include in rare category; (5) The policy of livestock conservation consists of the in-situ and ex-situ methods. In the level of implementation of the sustainability conservation, there were some aspects could be take into account such as agreement between government (political will and coordination), community (group farmer, empowering capital and marketing), and universities.